Reactivation of latent tuberculosis through modulation of resuscitation promoting factors by diabetes - Arpana Verma (Nature Portfolio, 2021)
Abstract The evidence of an association between diabetes and latent tuberculosis infection (LTBI) remains limited and inconsistent. Thus, the study aims to delineate the role of diabetes in activation of latent tuberculosis infection. Murine model of latent tuberculosis and diabetes was developed, bacillary load and gene expression of resuscitation promoting factors (rpfA-E) along with histopathological changes in the lungs and spleen were studied. Treatment for LTBI [Rifampicin (RIF) + Isoniazid (INH)] was also given to latently infected mice with or without diabetes for 4 weeks. Diabetes was found to activate latent tuberculosis as the colony forming unit (CFU) counts were observed to be > 104 in lungs and spleen. The gene expression of hspX was downregulated and that of rpfB and rpfD was observed to be upregulated in latently infected mice with diabetes compared to those without diabetes. However, no significant reduction in the CFU counts was observed after 4 weeks of treatment with RIF and INH. Diabetes helps in the progression of LTBI to active disease mainly through altered expression of resuscitation promoting factors rpfB and rpfD, which can serve as important targets to reduce the shared burden of tuberculosis and diabetes.